2009
DOI: 10.5688/aj730101
|View full text |Cite
|
Sign up to set email alerts
|

The Silver Tsunami is Coming: Will Pharmacy Be Swept Away with the Tide?

Abstract: It's been called the silver tsunami, the age wave, the geriatric imperative, among others. It is the aging baby boomers and the first of this cohort turns 65 years old in 2011. From a health care perspective, the numbers are scary. Seventy-six million boomers will enter the fragmented, under funded health care arena for older people. Today the elderly constitute 12% of the US population and use approximately 35% of all medications. Medication use will likely grow with increased use of multiple medications to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 2 publications
3
51
0
Order By: Relevance
“…The acceptance rate in our study is consistent with other studies that have reported an acceptance rate of 64% to 97.9% 12-19. All recommendations were verbally presented to the physician.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The acceptance rate in our study is consistent with other studies that have reported an acceptance rate of 64% to 97.9% 12-19. All recommendations were verbally presented to the physician.…”
Section: Discussionsupporting
confidence: 91%
“…All recommendations were verbally presented to the physician. In two studies evaluating written versus oral recommendations made by pharmacy students, it was found that verbal recommendations had a higher acceptance rate 18-19. Pound and Miller reported an 82.8% acceptance rate of verbal recommendations compared to 54.2% of written recommendations (p<0.0001) 18.…”
Section: Discussionmentioning
confidence: 98%
“…By 2031, the proportion of the population over 65 will nearly double. (1) Undeniably, the “Silver Tsunami” (2) will have consequences on the health care provided in EDs.…”
Section: Introductionmentioning
confidence: 99%
“…The aging of the population in the USA has been called a “silver tsunami” [16] and an “aging revolution” [17], and as such it has both health and economic implications [18]. Given the prevalence and impact of AF, it is incumbent upon physicians to use appropriate modalities and resources to care for this growing and particularly vulnerable population.…”
Section: Discussionmentioning
confidence: 99%